Therapeutic effects of axitinib, an anti-angiogenic tyrosine kinase inhibitor, on interstitial cystitis - Jung Hyun Shin; Chae-Min Ryu; Hwan Yeul Yu; Yang Soon Park; Dong-Myung Shin; Myung-Soo Choo (Scientific Reports, 2023)
Abstract To investigate the therapeutic effects of axitinib, a tyrosine kinase inhibitor, in an interstitial cystitis (IC) rat model. IC patients with or without Hunner lesion and non-IC controls were enrolled (n = 5/group). Bladder tissues were stained with vascular endothelial growth factor (VEGF), VEGF receptor 2 (VEGFR-2), platelet-derived growth factor (PDGF), and PDGF receptor B (PDGFR-B). The IC group showed extensive VEGFR-2 and PDGFR-B staining compared with controls. Next, ten-week-old female Sprague Dawley rats were divided into three groups (n = 10/group): sham, hydrochloride (HCl), and axitinib groups. One week after HCl instillation (day 0), the axitinib group received oral axitinib (1 mg/kg) for five consecutive days and pain was evaluated daily. Bladder function, histology and genetics were evaluated on day 7. The pain threshold significantly improved 3 days after axitinib administration. Axitinib decreased non-voiding contraction and increased the micturition interval and micturition volume and alleviated urothelial denudation, angiogenesis, mast cell infiltration, and fibrosis. HCl instillation increased the expression of tyrosine kinase receptors, including VEGFR-2 and PDGFR-B; axitinib administration inhibited their expression. Oral administration of axitinib improved pain, voiding profiles, and urothelial integrity by inhibiting angiogenesis in IC rat model. Axitinib may have potential therapeutic efficacy in IC patients.